Testing information security management system tool v2.1.1.0 based on ISO 27001:2005 [electronic resource] - 582138 Shehu, Abdulrahman Mustafa (2012)
Thesis (Sarjana Kejuruteraan Perisian) - Universiti Teknologi Malaysia, 2012